Cost of illness for neuromuscular diseases in the United States. Issue 3 (28th January 2014) - Larkindale, Jane; Yang, Wenya; Hogan, Paul F.; Simon, Carol J.; Zhang, Yiduo; Jain, Anjali; Habeeb‐Louks, Elizabeth M.; Kennedy, Annie; Cwik, Valerie A.
ABSTRACT Introduction: We conducted a comprehensive study of the costs associated with amyotrophic lateral sclerosis (ALS), Duchenne muscular dystrophy (DMD). and myotonic dystrophy (DM) in the U.S. Methods: We determined the total impact on the U.S. economy, including direct medical costs, nonmedical costs, and loss of income. Medical costs were calculated using a commercial insurance database and Medicare claims data. Nonmedical and indirect costs were determined through a survey of families registered with the Muscular Dystrophy Association. Results: Medical costs were driven by outpatient care. Nonmedical costs were driven by the necessity to move or adapt housing for the patient and paid caregiving. Loss of income correlated significantly with the amount of care needed by the patient. Conclusions: We calculated the annual per‐patient costs to be 63, 693 for ALS, 50, 952 for DMD, and 32, 236 for DM. Population‐wide national costs were 1, 023 million (ALS), 787 million (DMD), and 448 million (DM). Muscle Nerve49:431–438, 2014